Tarass Boulba - Gogol, Nikolai Vasilevich, 1809-1852; Viardot, Louis, 1800-1883 (Salt Lake City, UT : Project Gutenberg, 2004)
"Tarass Boulba" by Nikolai Vasilevich Gogol is a historical novella written in the early 19th century. The narrative delves into the lives and customs of the Zaporozhian Cossacks, centered around the titular character, Tarass Boulba, who is a fervent and traditional Cossack warrior. The plot explores themes of loyalty, family, and the adventurous, often brutal life of the Cossacks against the backdrop of their historical context. The opening of "Tarass Boulba" introduces us to the eponymous character as he greets his two sons, Ostap and Andry, upon their return from seminar studies. Instead of a warm reunion, it quickly devolves into a rough, playful fight, showcasing Boulba's gruff but affectionate nature. The narrative sets the tone for Boulba's rugged masculinity and his desire to mold his sons into fearless warriors. As he expresses discontent with the academic life they have led, he quickly resolves to send them to the Cossack camp, or "setch," where he believes they will gain the true essence of Cossack life. This sets the stage for the dynamics of family, tradition, and the impending adventures that await them in the Cossack warrior lifestyle. (This is an automatically generated summary.)
Release date is 2004-10-19
Produced by Ebooks libres et gratuits at http://www.ebooksgratuits.com
Keywords: Cossacks -- Fiction; Ukraine -- Fiction